Causality Relationship between Interest Rate of Deposit Banks and Profit Share Rate of Islamic Banks in Turkey - Yüksel, Serhat; Canöz, İsmail; Özsarı, Mustafa (IKONOMIKA, 2017)
The popularity of Islamic banking is increasing day by day. On the other hand, some people also criticized this system in some aspect. One of the criticism is that profit sharing rates of Islamic banks are similar to interest rate of deposit banks. While considering this issue, this study aims to identify the causality relationship between profit sharing rate and interest rate in Turkey. Within this scope, monthly, quarterly, 6-months and yearly data for the period between 2000 and 2016 was analyzed separately. In addition to this situation, Toda Yamamoto causality analysis was used in this study so as to achieve this objective. According to the results of the analysis, it was determined that there is a significant causality relationship between these rates. In other words, it was concluded that interest rate of the deposit banks is the main indicator of the profit share rate of Islamic banks in Turkey. The main reason behind this situation is that indicators in the market affect both deposit banks and Islamic banks. Therefore, it is inevitable that deposit rates and profit share rates will be similar when deposit banks and Islamic banks perform in the same market.